Progress in heliostat development. (August 2017) - Pfahl, Andreas; Coventry, Joe; Röger, Marc; Wolfertstetter, Fabian; Vásquez-Arango, Juan Felipe; Gross, Fabian; Arjomandi, Maziar; Schwarzbözl, Peter; Geiger, Mark; Liedke, Phillip
Graphical abstract: Highlights: 13 commercial heliostats and 8 under development are presented. Literature review of field layout, canting, control, qualification, and cleaning. Advances in wind load determination have been made in recent years. Cost below 100 USD/m 2 is achieved, even 75 USD/m 2 seem to be realistic. Abstract: Strong efforts are being made to drive heliostat cost down. These efforts are summarised to give an update on heliostat technology comprising: determination of wind loads, heliostat dimensioning, solutions for the different sub-functions of a heliostat, a review of commercially available and prototype heliostat designs, canting, manufacturing, qualification, heliostat field layout, and mirror cleaning. There is evidence that commercial heliostat costs have dropped significantly in the past few years, with commercial suppliers of heliostat technologies now claiming heliostat field costs around 100 USD/m 2 . With new approaches even target cost of 75/m 2 seem to be realistic.